Hak-Hak Reproduksi Perempuan dalam Islam - Mimin Mintarsih; PITROTUSSAADAH PITROTUSSAADAH (Jurnal Studi Gender dan Anak, 2022)
Indonesia is known as a country with the highest Mother Mortality Rate in South East Asia. According to the Women’s Health Foundation (YKP) the main causes of death are bleeding (46,7%), Eclampsia (14,5%), and infection which can be treated quickly. In addition, AKI is also caused because pregnant women are helped by incompetent people. Women’s reproductive health problems should require the involvement and care of many parties, families, communities, religious leaders, medical experts, law officers, and policy makers. Actually, it is normal if the topic is about reproduction health because it is the main problem for the women. The reproduction organ and function is the main distinction between men and women. But then the point is not about the anatomy and physic only. It mainly about how to sue the unbalanced reality relationship that can cause the women is unhealthy in implementing their reproduction function. In Islamic history, there are so many interpretations (Tafsir) that written by the priests in order to explain Al-Quran. The interpretations sometimes contain opinions, ideas, or quotations that discuss gender distinction in interpreting Al-Quran that can result in gender discrimination in the tafsir literature that the Moslems get. The understanding of women reproduction rights that is socialized by the priests really helps the understanding of the protection and prevention of mother mortality in the society that still has strong belief of their religion. In Islam, women reproduction rights are the rights that must be guaranteed because of its reproduction function. Quantitatively, the rights are balanced with the men’s rights as doer of reproduction function. Nowadays, the religion interpretation plays very strategic role to reinforce gender equality. The interpretation of this women reproduction rights contains several rights that have to guarantee the reproduction function. Moreover, if we know very high risk that the women have in implementing their reproduction function namely pregnancy, giving a birth and breast feeding. Religion exists to give secure peaceful and blessing feeling and to reinforce justice. Now, it’s time for Al-Quran and Hadits interpreter are demanded to involve intensely in order to overcome the high rate of violence in social area and exclusively in domestic area, that full of violence to the women. Reinterpretation of theological view and understanding of the right is no doubt.